2022
DOI: 10.1038/s41598-022-13371-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 waves: variant dynamics and control

Abstract: The waves of COVID-19 infections driven by its variants continue to nullify the success we achieved through efficacious vaccines, social restrictions, testing and quarantine policies. This paper models the two major variants-driven waves by two sets of susceptible-infected-quarantined-recovered-vaccinated-deceased coupled dynamics that are modulated by the three main interventions: vaccination, quarantine and restrictions. This $$SI^2Q^2R^2VD$$ S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Our results indicate that the second and third waves were more serious than the other waves. This correlates with the increase in the severity of disease and community transmission that was observed with Alpha and Delta variants, respectively [ 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our results indicate that the second and third waves were more serious than the other waves. This correlates with the increase in the severity of disease and community transmission that was observed with Alpha and Delta variants, respectively [ 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 90%
“…Several studies suggested that the COVID-19 surges appeared as a result of mutations in the SARS-CoV-2 virus and the emergence of new variants that are more virulent and transmissible [35][36][37][38][39]. The occurrence of mutations in the SARS-CoV-2 viral genome during replication is a natural phenomenon that has led to a number of novel variants [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The vaccination is one of the most effective ways to protect from infectious diseases. The development of vaccines against COVID-19 proved successful in preventing symptomatic infection and illness; however, despite the availability of vaccines, many countries experienced multiple COVID-19 waves, largely caused and driven by emerging new VOCs [ 27 ]; they prolong the continuation of the disease, leading to patient deaths, economic losses and a further burden on public health systems [ 4 ]. Globally, five COVID-19 waves were observed during the study period, from 1 August 2020 to 31 December 2021 [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main task of parameter estimation is to find the best-fit parameters to characterize physical processes and reproduce experiments 136 138 . To develop data-driven models, one can optimize the fit of a collection of parameters iteratively to a given dataset with random disturbance 137 , 139 , which explores the parameter space extensively and limits the number of non-convergent solutions 131 .…”
Section: Analysis Of Dynamic Modelingmentioning
confidence: 99%
“…There are some other control strategies that use feedback control laws based on nonlinear models. For example, a positive semi-definite Lyapunov function, whose gradient requires to be negative semi-definite, can be designed to calculate the controlled vaccination rate that asymptotically stabilizes Covid infection 138 .…”
Section: Analysis Of Dynamic Modelingmentioning
confidence: 99%